Analysis of Urea Fertilizer Production, Pricing, and Distribution in India in 2023: A Global and Domestic Perspective - Shivam Satyawan Madrewar; Snehal Sathe; Shlok Dongare; Swapnil Subhash Bade; Payal Navnath Bandgar; Sakshi Sharad Jagadale; Anuja Raghunath Gamane (International Journal of Global Sustainable Research, 2024)
This research paper analyzes the trends in urea fertilizer production, pricing, and distribution in India throughout 2023, with a focus on international market dynamics. The study highlights the fluctuations in global urea prices, domestic production and import figures, state-wise fertilizer requirements, and the performance of listed fertilizer companies. The paper also examines the impact of these factors on domestic prices, sales, and availability across various Indian states. This research aims to provide valuable insights for policymakers, industry stakeholders, and agricultural planners, ensuring efficient fertilizer management and availability. The analysis draws from government reports, industry data, and market trends, offering a comprehensive understanding of the urea fertilizer sector’s performance in India amidst changing global fertilizer prices